Argia sertaneja sp. nov. (Odonata: Coenagrionidae) from Northern Minas Gerais state, Brazil - Vilela, Diogo Silva; Jacques, Gabriel De Castro; Souza, Marcos Magalhães De (Zootaxa, 2024)
Argia sertaneja sp. nov. (BRAZIL, Minas Gerais state, Chapada Gaúcha, Grande Sertão Veredas National Park, Vereda lodging (15.iv.2023, 15°11’14.7”S 45°41’01.7”W, 807 m asl, M.M. Souza leg., Coleção Biológica de Vespas Sociais—CBVS) is described, illustrated, and diagnosed. The new species can be separated from its congeners by the wide morphology of male cercus, and shape of female hind lobe of prothorax and mesostigmal lobes.